CORRELATION OF ZAKAT DISTRIBUTION WITH GINI INDEX: MAXIMIZING THE POTENTIAL OF ZAKAT FOR EQUITABLE INCOME DISTRIBUTION IN INDONESIA - Nisa Rahma Fadila (Airlangga International Journal of Islamic Economics and Finance, 2019)
This study aims to determine the correlation of zakat distribution with the Giniindex. The unequal distribution of income shown by the Gini index is an economicproblem facing Indonesia today. Zakat as an instrument in the Islamic economicsystem can be a solution for equal distribution of income in Indonesia. The dataanalysis technique used is Pearson correlation analysis. The results of this analysisindicate that the distribution of zakat has a significant correlation with the Giniindex.